Abbott & Costello. The complete Universal Pictures collection. [Discs 5-6] [videorecording (DVD)] - Kenton, Erle C., 1896-1980; Lamont, Charles, 1895-1993; Abbott, Bud, 1897-1974; Costello, Lou; McDonald, Grace, 1921-; Kellaway, Cecil, 1891-1973; Pallette, Eugene, 1889-1954; Simms, Ginny; Treacher, Arthur, 1894-1975 (Universal Studios Home Entertainment, 2008)
It ain't hay: Bud and Lou accidentally kidnap the famous racehorse, Tea Biscuit. Hit the ice: Unwittingly involved in a robbery, Bud and Lou trail the crooks to the Sun Valley ski resort. In society: Bud and Lou find themselves in hot water after a plumbing job goes wrong at a high society bash. Here come the co-eds: Bud and Lou head to campus and attempt to save Bixby College from closing down.